Why there will be no Helsinki Ii–-and why Confidence Building with Putin's Russia is a Bad Idea. Issue 1 (June 2016) - Freudenstein, Roland
Over the last 10 years, Russia under Putin has turned into an illiberal empire that is determined to weaken the West as a precondition for its own survival. This fact is still not fully appreciated by those Western leaders who believe that a return to cooperation with Russia is both necessary and possible. Germany's Social Democrats are particularly prominent among these leaders. They intend to use Germany's 2016 presidency of the Organization for Security and Co-operation in Europe to lay the groundwork for a step-by-step confidence-building effort, eventually leading to a new European security architecture. Such hopes are utterly futile. They are based on old illusions about detente and Ostpolitik. Moreover, they are understood by the Kremlin to be signs of weakness and appeasement. Instead of answering every Russian act of aggression with new offers for talks, the West should prepare for a long confrontation with Russia, maintain unity, and strengthen defence and deterrence.